Tantangan Eksekusi Waris Atas Kepemilikan Saham Dalam Perusahaan Keluarga - Rayi Kharisma Rajib; Mutiara Rizqi Faviola; Sheilla Lutfiyah Faradila (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to analyze the legal problems in the execution of inheritance regarding share ownership in family companies in Indonesia. The research method used is normative legal research with statutory and conceptual approaches. The results indicate that the main challenge in executing share inheritance lies in the conflict between inheritance laws (Civil Code or Islamic Law) and the provisions of the company's Articles of Association, as well as the Law on Limited Liability Companies. The scope of the research focuses on procedural obstacles when heirs enter the shareholder structure, which often trigger internal conflicts and threaten business continuity (going concern). The conclusion of this study emphasizes the need for regulatory synchronization and the drafting of buy-back clauses or restrictions on the transfer of share rights within the Articles of Association to ensure legal certainty for heirs and corporate stability. The effectiveness of the execution heavily depends on mediation among heirs and compliance with the principles of information disclosure within the company.